A BIBLIOGRAPHIC STUDY FOR MANAGEMENT CONTROL SYSTEMS ON JOURNAL OF MANAGEMENT ACCOUNTING RESEARCH - Suham Cahyono (Jurnal Bisnis dan Akuntansi, 2023)
This study aims to trace the track record of management control system research found in reputable international journals (Journal of Management Accounting Research). To obtain accurate research results, we documented research published during the 2021 period of 45 reputable articles. We found that research in the field of management control systems is a very interesting issue to study. Several previous findings strengthen the trend of management accounting research, especially in the field of MCS which is mostly associated with internal and external resources of the company. In addition, MAR research with the MCS theme makes an important contribution not only to the development of the complexity of the existing literature, but also becomes material for study by experts, stakeholders, and the government in formulating policies and strategies related to current and future corporate issues.